Intravaginal misoprostol 100 µg for cervical ripening and induction of labour in nulliparous women with term pregnancy and unfavourable cervix: a case series report - Awoyesuku, Peter A.; Ohaka, Chinweowa; Amadi, Simeon C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical ripening is a prerequisite for induction of labour in women adjudged to have an unfavourable cervix. Misoprostol administered intravaginally has previously been shown to be effective for cervical ripening and labour induction. It is often used in dosages of 25 µg or 50 µg in single or repeated dose regimen as per guidelines. Higher doses or shorter dosing intervals were reportedly associated with a higher incidence of side effects, especially uterine hyperstimulation syndrome. Studies and clinical experience have shown that 50 µg dose was not as effective in nulliparous women as it was in multiparous women, which implies that this dose might not be optimal for nulliparous women. We report a series of seven carefully selected patients in whom we used 100 µg of misoprostol intravaginally for cervical ripening and induction of labour at term. We achieved a short induction delivery interval, had good improvement in Bishop’s score, with less need for oxytocin augmentation and good safety parameters.